Development and characterization of lime-based stucco for modern construction and restoration applications based on ancient stuccoes from the “El Cerrito” pyramid, Querétaro, Mexico - Mario E. Rodriguez-Juarez; Edgar Perez-Diaz; Guillermo I. Lopez-Dominguez; Veronica Leyva Picazo; Daniel Valencia-Cruz; Beatriz M. Millan-Malo; Mario E. Rodriguez-Garcia (Case Studies in Construction Materials, 2022)
This work studied the physical-chemical characteristics of two lime-based stucco samples extracted from the “El Cerrito” archeological site in Querétaro, Mexico. Their compositional analyses are consistent with calcite, labradorite (clay mineral), sand size quartz and volcanic lithics, and organic compounds. Scanning Electron Microscopy (SEM) images confirmed the use of micro and submicron natural fibers. Energy Dispersive Spectroscopy semi-quantitative analysis (EDS-SEM) showed Al, Mg, Ca, C, Si, K, and O as the major element components. Inductively Coupled Plasma (ICP) quantitative analysis found Ca, Al, Fe, Mg, and K as the major components, and Ba, P, S, Sr, Mn, Cr, and V, as minor and trace elements that produce a compelling fingerprint. X-ray diffraction patterns reveal that these stuccoes are formed by calcite and labradorite crystalline phases. These analyses were used to develop and reproduce a new stucco formulation that can be used to conserve and restore archeological buildings and as modern wall finishing. The new stucco is a heterogeneous mixture of calcium hydroxide, pozzolan (alunite-kaolinite), fine quartz sand, and volcanic lithics as an aggregate, and soluble and insoluble natural fibers obtained from nopal pads as additives. A step-by-step methodology to prepare and apply the newly formulated stucco in a modern house as a wall finishing is reported. Pozzolan, calcium hydroxide, and water react to produce the pozzolanic effect acting as a non-hydraulic cement, while calcium hydroxide reacts with the atmospheric CO2 to form calcium carbonate. Portlandite conversion to calcite and the pozzolanic effect to obtain labradorite were shown by X-ray analysis and high-resolution SEM images of the newly applied stucco.